Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1039/c6ra28719k
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the energy transfer mechanism in bismuth co-activation of LaInO3:Sm3+/Ho3+ nanophosphor for color-tunable luminescence

Abstract: A series of single-phased and color tunable LaInO3:Bi3+,Ho3+/Sm3+ nano phosphors were synthesized via a cost effective and low temperature chemical route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 47 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…In addition, it is found that, there is a decrease in grain size of doped and codoped samples in comparison with that of undoped sample which may be due to grain growth inhibition during sample preparation. [ 39 ] Additionally, using ImageJ software, it was found that the agglomerates average grain size was around 80 nm, as shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is found that, there is a decrease in grain size of doped and codoped samples in comparison with that of undoped sample which may be due to grain growth inhibition during sample preparation. [ 39 ] Additionally, using ImageJ software, it was found that the agglomerates average grain size was around 80 nm, as shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…The average bond length of Ga-O in GaO 6 is 1.975 A; while La 3+ is 8-coordinated by O atoms with average bond length of 2.62 A for La-O. The minor changes in lattice parameters of single doped Bi 3+ , Cr 3+ and co-doped in LaGaO 3 when compared with undoped LaGaO 3 depends on ionic radii 22. The radius of Bi 3+ (r ¼ 1.03 A, coordination number, CN ¼ 6) is similar to that of La 3+ (r ¼ 1.16 A, CN ¼ 8), while the radius of Cr 3+ (r ¼ 0.61 A, CN ¼ 6) is comparable to that of Ga 3+ (r ¼ 0.47 A, CN ¼ 6),27 thus in Bi 3+ -Cr 3+ co-doped LaGaO 3 , Bi 3+ mostly likes to take La site and Cr 3+ likes to take Ga site.…”
mentioning
confidence: 95%
“…Research reports also show that along with Eu 2+ , Ce 3+ ; Bi 3+ could be used as sensitizer ion to produce abundant and tunable emission colors including white via adjusting doped ion concentrations. [18][19][20][21][22] Trivalent chromium (Cr 3+ ) is widely used as a luminescent dopant in various materials. Chromium is a low-cost activator, which can provide deep red color and bright luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…However, low initial cost outlay and low production risk (defective batch can easily be identified and disposed of) are some of the advantages of batch process. The batch processes currently in place for complex oxide preparation are solvothermal 141 , sol-gel 142 , polyol [143][144] , solid-state reaction 145 . In stark contrast, however, starting materials pass through unit operation/unit process in a repeated and uninterrupted manner in continuous processing.…”
Section: Scalabilitymentioning
confidence: 99%